Akuntansi Hak dan Kewajiban: Refleksi Akuntansi Nelayan Juragan Muslim di Kawasan Teluk Tomini - Niswatin, Niswatin; Yusuf, Nilawaty; Arsyad, Nur Fadilah; Olatapa, Mohamad Yuda; Bahsuan, Siti Aisyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aims to reveal the meaning of accounting for muslim skipper fishermen in the tomini bay area. Symbolic interactionism is the research method used in this research. The symbolic interactionist approach is also used as a data collection technique as well as a unit of analysis. The data used are (1) the results of interviews with the boat owner as ship owners and retainers (2) results of observations of fishermen's activities and interactions with crew members and their environment (3) documents such as worksheets and financial reports. This research determines that there is a mutual need for interaction between the boat owner and the captain or crew member. Boat owner who has the right to share business profits fairly to the crew in the form of transparent accounting records and crew members who have the obligation to carry out their responsibilities to the boat owner.